REDESCRIPCION DEL HUEVO, ULTIMO ESTADIO LARVAL Y LA PUPA DE ARGYROPHORUS ARGENTEIS BLANCHARD, 1852 Y DESCRIPCION DEL ULTIMO ESTADIO LARVAL Y PUPA DE ETCHEVERRIUS CHILIENS1S (GUERIN, 1832) Y AUCA NYCTEROPUS (REED, 1877). (LEPIDOPTERA: NYMPHALIDAE) (Acta Entomológica Chilena, 2022)
The last larval instar and pupac of E. chiliensis and A. nycteropus are described and illustratedfor the first time in this paper; while the egg, last larval instar and pupa of A. argenteus are alsoredescribed. Illuslrations and etological and biological observations are included. Stipa speciosaTrinius et Ruprecht (Gramineae) is reponed as their host-plant.